The performance of construction partnering projects in Malaysia - Ali, A.S.; Mohd-Don, Z.; Alias, A.; Kamaruzzaman, S.N.; Pitt, M. (2010)
The construction industry in Malaysia is a competitive high-risk business as the nation strives to emerge as a developed country. The number of construction companies in the country has been skyrocketing in recent years, including the setting up of many small companies in rural areas. These small companies often face enough problems attaining a good reputation and credibility for themselves, let alone competing with their established counterparts which have mostly been in the industry for longed. The recent hike in the price of materials, such as steel and cement, also poses a threat to small companies with financial constraints. The bigger companies, on the other hand, may at times face a shortage of expertise or a sufficient workforce to perform certain tasks. The construction partnering concept appears to be an ideal solution to the predicaments mentioned, by ensuring mutual benefit to all parties involved by creating a win - win situation. This paper will examine, the performance of construction partnering projects in Malaysia, in relation to the satisfaction level of construction industry players, and the dominant benefits associated with construction partnering. This was done by first identifying the problem and objectives of the research through a thorough literature review based on reliable sources, followed by a comprehensive quantitative data collection through questionnaire surveys. The data was then processed using descriptive analysis to tie up with the objectives, followed by formulating of conclusions. The research revealed that, majority of the respondents agreed that, communication among parties and functionality are the two most dominant variables in determining the performance of a partnering project. In addition, the three dominants benefit and identified the improved culture, increased satisfaction and potential for innovation.